Porewater exchange and iron transformation in a coastal groundwater system: a field investigation, driving mechanisms analysis, and conceptual model - Cao, Wenran; Hofmann, Harald; Yan, Guanxi; Scheuermann, Alexander (Frontiers in Marine Science, 2024)
The high concentration of dissolved iron (Fe) in coastal waters triggers Lyngbya blooms in the Moreton Bay region of Southeast Queensland, Australia. Previous studies have provided a restricted understanding of how land-derived Fe is transported and then transformed into other forms (e.g., Fe oxides) before its release into the ocean. Here, a field investigation was conducted at a sandy beach on the northern end of Deception Bay, Queensland, Australia, focusing on porewater exchange and Fe transformation. This study revealed that tides provided a significant mechanism for driving the groundwater-seawater mixing in the intertidal area. Such forcing formed an upper saline plume (USP) with high dissolved oxygen (DO), creating a dynamic reaction zone for Fe oxidation and precipitation beneath the USP. The spatial distribution of Fe oxides highlighted a substantial Fe content in the subsurface, providing concrete evidence for the transformation of Fe from an aqueous state to a solid form. It also exhibited a low-permeable area that served as a geochemical barrier, absorbing chemical components like phosphate. These findings can assist in constructing a more accurate transport model that couples physical and geochemical processes to quantify the mechanisms driving Fe transformation in coastal areas and further deepen our comprehension of the hydrogeochemical functionalities in land-ocean connectivity via groundwater.